2021
DOI: 10.1111/tri.13825
|View full text |Cite
|
Sign up to set email alerts
|

Guiding therapeutic plasma exchange for antibody‐mediated rejection treatment in lung transplant recipients – a retrospective study

Abstract: Summary Antibody‐Mediated Rejection (AMR) due to donor‐specific antibodies (DSA) is associated with poor outcomes after lung transplantation. Currently, there are no guidelines regarding the selection of treatment protocols. We studied how DSA characteristics including titers, C1q, and mean fluorescence intensity (MFI) values in undiluted and diluted sera may predict a response to therapeutic plasma exchange (TPE) and inform patient prognosis after treatment. Among 357 patients consecutively transplanted witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…A positive cutoff of 1000 MFI was used to identify positive DSA specificities. Antibody titers were determined by performing serial fourfold dilutions using PBS and EDTA‐treated sera (undiluted, 1:4, 1:16, 1:64, etc.,) as previously described 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive cutoff of 1000 MFI was used to identify positive DSA specificities. Antibody titers were determined by performing serial fourfold dilutions using PBS and EDTA‐treated sera (undiluted, 1:4, 1:16, 1:64, etc.,) as previously described 27 …”
Section: Methodsmentioning
confidence: 99%
“…Antibody titers were determined by performing serial fourfold dilutions using PBS and EDTA-treated sera (undiluted, 1:4, 1:16, 1:64, etc.,) as previously described. 27…”
Section: Hla Donor-specific Antibody Measurementmentioning
confidence: 99%
“…Following this report, many laboratories have adopted testing of at least one serum dilution when antibodies of interest have mean fluorescence intensity (MFI) values >12 000 to 15 000 MFI units. More recently, Timofeeva et al 68,69 reported a successful implementation of this approach in exploring transplantation of highly sensitized heart transplant candidates and guiding ABMR therapy in lung transplant recipients.…”
Section: Approaches To Quantify Hla Antibody Strengthmentioning
confidence: 99%
“…Studies in heart and lung transplantation evaluating the value of measuring HLA-DSAs (and C1q-binding status) before and after treatment of ABMR are sparse, uncontrolled and of small sample size. These have shown on selected patients with ABMR that HLA-DSA MFI, titer and C1q-binding capacity were significantly decreased after plasmapheresis, intraveinous immunoglobulin þ/proteasome inhibitors (including Bortezomib) [51][52][53].…”
Section: Human Leukocyte Antigen-donor-specific Antibodies For Precis...mentioning
confidence: 98%